Readings in Ethnomusicology. Two collections of papers presented at Ethnomusicology Symposia 2010 and 2011. Mitchel Strumpf and Imani Sanga (eds.). University of Dar es Salaam, Dept. of Fine and Performing Arts. 153pp.; 193pp. - Tracey, Andrew (International Library of African Music, 2012)
pages: 190
Keywords: African Music